Use of the European Organisation for Research and Treatment of Cancer multiple myeloma module (EORTC QLQ-MY20): a review of the literature 25 years after development - Forde, K.; Cocks, K.; Wells, J. R.; McMillan, I.; Kyriakou, C. (Blood cancer journal (New York), 2023)
The European Organisation for Research and Treatment of Cancer Quality of Life Multiple Myeloma Questionnaire (EORTC QLQ-MY20) was developed in 1996 to assess health-related quality of life (HRQoL) in patients with multiple myeloma. Since its development new therapies have prolonged survival in patients with myeloma and new combination agents are likely to impact HRQoL outcomes and its measurement. The aim of this review was to explore the use of the QLQ-MY20 and reported methodological issues. An electronic database search was conducted (1996-June 2020) to identify clinical studies/research that used the QLQ-MY20 or assessed its psychometric properties. Data were extracted from full-text publications/conference abstracts and checked by a second rater. The search returned 65 clinical and 9 psychometric validation studies. The QLQ-MY20 was used in interventional ( n = 21, 32%) and observational ( n = 44, 68%) studies and the publication of QLQ-MY20 data in clinical trials increased over time. Clinical studies commonly included relapsed patients with myeloma patients ( n = 15, 68%) and assessed a range of combinations therapies. QLQ-MY20 subscales (disease symptoms [DS], side effects of treatment [SE], future perspectives [FP], body image [BI]) were defined as secondary ( n = 12, 55%) or exploratory ( n = 7, 32%) trial endpoints, particularly DS ( n = 16, 72%) and SE ( n = 16, 72%). Validation articles demonstrated that all domains performed well regarding internal consistency reliability (>0.7), test-reset reliability (intraclass correlation coefficient > =0.85), internal and external convergent and discriminant validity. Four articles reported a high percentage of ceiling effects in the BI subscale; all other subscales performed well regarding floor and ceiling effects. The EORTC QLQ-MY20 remains a widely used and psychometrically robust instrument. While no specific problems were identified from the published literature, qualitative interviews are ongoing to ensure new concepts and side effects are included that may arise from patients receiving novel treatments or from longer survival with multiple lines of treatment.